2009
DOI: 10.1371/journal.pone.0006330
|View full text |Cite
|
Sign up to set email alerts
|

KCNE1 and KCNE3 β-Subunits Regulate Membrane Surface Expression of Kv12.2 K+ Channels In Vitro and Form a Tripartite Complex In Vivo

Abstract: Voltage-gated potassium channels that activate near the neuronal resting membrane potential are important regulators of excitation in the nervous system, but their functional diversity is still not well understood. For instance, Kv12.2 (ELK2, KCNH3) channels are highly expressed in the cerebral cortex and hippocampus, and although they are most likely to contribute to resting potassium conductance, surprisingly little is known about their function or regulation. Here we demonstrate that the auxiliary MinK (KCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Although the cardiac function of KCNE1 has been mostly explored in previous studies, studies demonstrated that KCNE1 is also expressed in neuronal cells and regulates a neuronal K v channel function (18, 37). Because BACE1 is expressed at high levels in neurons as compared to other cell types (38), BACE1 may have more profound roles in regulating neuronal KCNE1‐and KCNE1‐regulated K v channels in neuronal cells under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the cardiac function of KCNE1 has been mostly explored in previous studies, studies demonstrated that KCNE1 is also expressed in neuronal cells and regulates a neuronal K v channel function (18, 37). Because BACE1 is expressed at high levels in neurons as compared to other cell types (38), BACE1 may have more profound roles in regulating neuronal KCNE1‐and KCNE1‐regulated K v channels in neuronal cells under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…7). In addition to KCNE2, studies showed regulatory roles of other KCNEs on neuronal Kv channels, including KCNE1 and KCNE3 (18, 37, 42, 43). Therefore, it will be very interesting to explore whether BACE1 and/or PS/γ‐secretase cleave these KCNEs and regulate neuronal Kv channels, as well as KCNE2.…”
Section: Discussionmentioning
confidence: 99%
“…Kv12.2 may, thus, also need a ␤-subunit for efficient glycosylation and cell surface expression. Another possibility is that, as a recent study showed using Xenopus oocytes (41), intrinsic KCNE1 and KCNE3 may down-regulate the cell surface expression of Kv12.2 in CHO cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, KCNE3 strongly inhibits hERG, again by an unresolved mechanism 17 , although the same KCNE3 substitution (R83H) that disrupts ability to constitutively open KCNQ1 channels and augment Kv3.4 currents 65 also blunts the ability of KCNE3 to inhibit hERG 66 . Interestingly, KCNE1 and KCNE3 are reported to form tripartite complexes with Kv12.2 (also termed ELK2 or KCNH3), inhibiting its surface expression and activation in Xenopus oocytes; this may also occur in mouse brain 67 .…”
Section: Kcne1 and Kcne3 Regulation Of Other Kv α Subunitsmentioning
confidence: 99%